Accuracy Comprehensive Review of Diagnostic Accuracy in Healthcare Services - AL-Mahrei, Salem Mana Ali; Algarea, Salem Mohammed; Alqerea, Hadi Mohammed; Almansour, Saleh Swaid Saleh; Alyami, Ali Obyan Mohammed; Alyami, Suwyyid Abyan Mohammed; Al Mutarid, Ali Hadi Dawood; Almansour, Hamad Mohammed Mansour; Alyami, Dohan Mohammed Hashan; Alsulaiman, Fayez Ali Saeed (Journal of Ecohumanism, 2024)
Accuracy of diagnosis is critical in health care because it determines the results of treatment, use of resources, and clinical management of patients. This review focuses on the potential determinants of diagnostic performance, present methods applied in diagnosing healthcare, and accuracy within domains. The recent studies and data analysis identified possible strengths, limitations, and improvement strategies. It also uses graphics and labeling to present trends and gaps. Finally, strategies are suggested to improve diagnostic accuracy to address the growing and new healthcare demands.